A Rare Case of Intra-Osseous Meningioma of the Sphenoid Bone - A Case Report - Ferdousi, Mahfuz Ara; Sharif, Md Mofazzal; Bahar, Hijbul; Mohiuiddin, AS; Hossain, ATM Mosharef; Banu, Sultana Gulshana (Ibrahim Medical College Journal, 2013)
A 42-year-old female patient presented with loss of vision and proptosis of her right eye. Computerized tomography (CT) scan revealed hyperostotic lesion involving the right sphenoid ridge, anterior clinoid process and roof and lateral wall of orbit with mass effect on the intraorbital contents. CT findings were suggestive of intra-osseous meningioma arising from right sphenoid bone. Later, MRI of the brain and orbit and histopathology of the lesion confirmed the case as an intra-osseous meningioma of the sphenoid bone. Though meningioma of tuberculum sella and primary calvarial meningioma were reported earlier, intraosseous meningioma of the sphenoid bone is rare. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14737 Ibrahim Med. Coll. J. 2012; 6(2): 73-75